(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
This paper is the result of two study-trips to Africa, which took place in Kenya between 2012 and 2013. During my first visit I lived in a village called Kiburanga, in the South of the country, while the second time I stayed in the Kenyan slum of Kibera and in particular in Mathare. The report I am presenting in this paper is about my survey in Kibera, which was part of a broad collaborative effort of many individuals; people participating to an association help themselves and the communities, especially in a slum. I’ll try to explain what those places really are: «Slums are the physical negation of everything». Infact, as Kapuscinski maintains introducing his research work: «This is therefore a book about Africa, but rather about some people from there-about encounters with them, and time spent together. The continent is too large to describe. It is a veritable ocean, a separate planet, a varied, immensely rich cosmos. Only with the greatest simplification, for the sake of convenience, can we say Africa. In reality, except as a geographical appellation, Africa does not exists».